Emergency department referrals from a provincial medical call centre: Is it more than just 1-800-go-to-emerg?. Issue 2 (March 2020) - Nataraj, Jonathon; Stempien, James; Netherton, Stuart; Wahba, Mark Yosri; Oyedokun, Taofiq Olusegun
ABSTRACT: Objective: HealthLine is Saskatchewan's provincial 24-hour health information and support telephone line. A proportion of HealthLine's callers are referred to the emergency department (ED) for further assessment. The purpose of this study was to gain insight into the appropriateness of these referrals and assess whether they increased the burden on an already strained ED system. Methods: A list of callers referred from HealthLine to Saskatoon EDs from January 1, 2014, to March 31, 2014 was obtained. This list was cross-referenced with Saskatoon Health Region registration data to determine which of those callers had been registered in one of the three Saskatoon EDs within 48 hours of the original call. Results: During the 90-day time period in question, 707/3, 938 (17.9%) of callers were referred by HealthLine to the ED. Out of those referred, 601 were identifiable and 358 attended the ED. Hospital charts were pulled for full data extraction and analysis of the 276 who met inclusion criteria. Of those who presented to the ED and met inclusion criteria, 60% had investigations performed while 66% received some form of treatment. The overall admission rate for the patient population studied was 12.0% v. 16% for non-referred patients. Referred pediatric patients had fewer investigations and treatments with a lower admission rate compared with the adult patients. Conclusion: The Saskatchewan HealthLine is doing an effective job at directing callers both to and away from EDs in Saskatoon and not overburdening our local EDs with unnecessary referrals.